Perancangan Interior One Stop Creative Photo Video Studio di Surabaya - Stanley Abednego (Intra, 2018)
In this modern era, the development of photography and videography are increasing rapidly along with its popularity amongst society. Lots of new communities of beginner to professional established. In addition, photography and videography are not only considered as a hobby nowadays, but it is also seen as a real job by the community. Thus, more facilities are needed to support all photography and videography activities. In Indonesia, enthusiasm towards photography and videography has been enlarging, especially in big cities. Surabaya is indeed one of them, along with the fact that Surabaya has many photography enthusiasts in the community. There are many services that offered for photography or photography activities. But, facilities that supported users to explore the world of photography and videography completely is not much.                Therefore, interior design of One Stop Creative Photo and Video Studio is proposed using the concept of bringing out the icons from the city of Surabaya, including the Kepanjen church, Tunjungan bridge, Tunjungan street, and Bungkul Park in accordance to trigger people to visit those unique locations of Surabaya. In addition, in this design concept adopt the characteristics of Surabayan people, such as brave, creative and dynamic.